Hyperosmolarity‐Induced Down‐Regulation of Claudin‐2 Mediated by Decrease in PKCβ‐Dependent GATA‐2 in MDCK Cells. Issue 11 (November 2015) - Ikari, Akira; Fujii, Naoko; Hahakabe, Shinya; Hayashi, Hisayoshi; Yamaguchi, Masahiko; Yamazaki, Yasuhiro; Endo, Satoshi; Matsunaga, Toshiyuki; Sugatani, Junko
<x xml:space="preserve">Abstract</x> Hyperosmolarity decreases claudin‐2 expression in renal tubular epithelial cells, but the molecular mechanism remains undefined. Here, we found that the hyperosmolarity‐induced decrease in claudin‐2 expression is inhibited by Go6983, a non‐selective protein kinase C (PKC) inhibitor, and PKCβ specific inhibitor in Madin‐Darby canine kidney II cells. Hyperosmolarity increased intracellular free Ca2+ concentration and phosphorylated PKCβ level, which were inhibited by RN‐1734, an antagonist of transient receptor potential vanilloid 4 channel. Phorbol 12‐myristate 13‐acetate, a PKC activator, decreased claudin‐2 expression. These results indicate hyperosmolarity decreases claudin‐2 expression mediated by the activation of RN‐1734‐sensitive channel and PKCβ. Hyperosmolarity decreased promoter activity of claudin‐2, which was inhibited by Go6983 and PKCβ inhibitor similar to those in real‐time PCR and Western blotting. The effect of hyperosmolarity on promoter activity was not observed in the construct of −469/−6, a deletion mutant. Claudin‐2 has hyperosmolarity‐sensitive region in its promoter, which includes GATA binding site. Hyperosmolarity decreased the nuclear level of GATA‐2, which was inhibited by Go6983 and PKCβ inhibitor. Mutation of GATA binding site decreased the basal promoter activity and inhibited the effect of hyperosmolarity. In contrast, the hyperosmolarity‐induced decrease in reporter activity and claudin‐2 expression were rescued by over‐expression of wild type GATA‐2. Chromatin immunoprecipitation assay showed that GATA‐2 bound to promoter region of claudin‐2. These results suggest that hyperosmolarity decreases the expression level of claudin‐2 via a decrease in PKCβ‐dependent GATA‐2 transcriptional activity in renal tubular epithelial cells. J. Cell. Physiol. 9999: 2776–2787, 2015. © 2015 Wiley Periodicals, Inc.